The Effectiveness of use methods and media on agricultural extensive in Lubuk Raja District of Ogan Komering Ulu Regency - Mutia Maryanti; Munajat, Munajat; Fifian, Fifian Permata Sari (International Journal of Social Science, 2022)
This study aims to analyze what methods and media are effective in delivering agricultural extension materials and how farmers respond to the use of media used by agricultural extension workers in Lubuk Raja District, OKU Regency. This research was conducted in Lubuk Raja District, Ogan Komering Ulu Regency. This research was carried out for 3 months, namely from January to March 2022. The location of the research was determined deliberately considering that in Lubuk Raja Subdistrict using methods and media for Agricultural Extension facilities. The method used in the research is the survey method. The sampling method used is a simple random method. The sampling process uses the Slovin formula where a population of 2150 people is taken as many as 215 people as samples. The results showed that agricultural extension with the discussion method got the best response from rubber farmers in Lubuk Raja sub-district with the highest number of agreeable responses, namely 215 respondents and 0 respondents who disagreed, while for the demonstration method there were 202 respondents who said yes and 13 respondents. who stated that they did not agree, on the widyawisata method as many as 139 respondents said yes they agreed and 76 respondents said they did not agree. The existence of results with very different amounts is due to several factors such as; natural or financial factors. The discussion method is stated to be more efficient because it does not use a lot of costs, while the widyawisata method gets the answer yes to agree at least from the respondents because this method requires greater costs than the discussion method and demonstration method, such as transportation and accommodation costs.